Enseigner la culture de l’autre: la tentation culturaliste - Machart, Regis Christian; Chin, Sin Zi (Université Abderrahmane Mira – Bejaia, 2014)
The Didactics of culture and interculturality often follows a solid approach, ignoring the fundamental diversity of each culture. Lecturers are confronted with a dilemma: How to teach the ‘culture’ of the Other without falling into the trap of stereotyping? This contribution analyses the discourse of French lecturers in Malaysia, a multicultural and multilingual country, and questions their theoretical framework of culture. It appears that more teaching material which takes into account agreater sense of diversity is needed for the classroom.